Evaluation of English Teaching Material for Senior High School - Astrini, Atik; Yeny Prastiwi; Muamaroh (PT. Banjarese Pacific Indonesia, 2023)
In Surakarta, English teachers use manuals to guide scholars and collaborate in the literacy process, and use it as a tonal resource to gain rich input into literacy. In order to improve the quality of English teaching in Indonesia, this study was conducted to measure whether two books used in high school,